Secure IT Systems : c - Buchegger, Sonja; Dam, Mads.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the proceedings of the 20th Nordic Conference on Secure IT Systems, held in Stockholm, Sweden, in October 2015. The 11 full papers presented together with 5 short papers in this volume were carefully reviewed and selected from 38 submissions. They are organized in topical sections named: cyber-physical systems security, privacy, cryptography, trust and fraud, and network and software security.
Keywords: Computer security; Data encryption (Computer science).; Biometrics; Computer software; Computer science; Systems and Data Security; Cryptology; Biometrics; Algorithm Analysis and Problem Complexity; Computers and Society